METHODS OF TREATMENT OF RESIDUAL CAVITY AFTER ECHINOCOCCECTOMY OF THE LIVER (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Despite significant advances in liver surgery, the introduction of new technical means in performing operations, in the immediate postoperative period in liver echinococcosis (LE) typical complications often occur (10-24% of cases) in the form of suppuration of the residual cavity (RC), the formation of external purulent and biliary fistulas. In this regard, improving the methods of diagnosing LE and its complications, as well as technical methods that can reduce the frequency of specific complications after echinococcectomy, is of great importance in the treatment of patients with this pathology. A large number of relapses of the disease and dissatisfaction (high toxicity, insufficient germicidal activity) with the results of intraoperative use of germicidal drugs, the duration of their exposure during surgery, sometimes with repetition of manipulation (multiple) forced us to look for new methods of cyst treatment.